전기노인 여성의 삶의 질 중 기운에 따른 건강행태와 영양상태 비교: 2019년, 2021년 국민건강영양조사 자료를 이용하여 - 정지영(Jiyoung Jeong); 양윤정(Yoon Jung Yang) (Journal of nutrition and health, 2023)
Purpose: This study aimed to identify the general characteristics, chronic diseases, health behavior, mental health, and nutritional status of young-old women based on their vitality. Methods: This study used data from the 2019 and 2021 Korea National Health and Nutrition Examination Survey (KNHANES). The subjects were 1,113 young-old women aged 65 to 74 years old. The health-related quality of life concept with an 8-item questionnaire was used to measure the quality of life. Subjects were categorized into 4 groups (always, often, sometimes, never) based on their vitality. General characteristics, chronic diseases, health behavior, dietary behavior, food intake, and nutrient intake were compared among the groups. Results: Age, education level, household income, employment, fruit intake, dietary supplements, abundance of food, and nutrition labeling recognition were associated with the vitality of the subjects. Young-old women with arthritis, diabetes, and osteoporosis displayed lower vitality. Moreover, subjective health status, exercise, activity restrictions, and average daily sitting hours were related to vitality, while no significant difference was found in vitality between smoking and drinking. In terms of mental health factors, higher vitality was associated with 6-8 hours of sleep, lower stress levels, and reduced depression. The high-vitality group exhibited a higher intake of potatoes, starch, mushrooms, fruits, meat, milk, animal oils, and beverages than the low-vitality group. Additionally, the group with higher levels of vitality showed a higher intake of protein, fat, saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids, n-6 fatty acids, dietary fiber, sugars, phosphorous, potassium, magnesium, iron, zinc, and riboflavin. Conclusion: This study suggests that the vitality of young-old women is related to socioeconomic factors, health behavior, mental health, and food intake. To maintain a vibrant lifestyle in elderly women, it is necessary to have social and economic stability, prevent arthritis, diabetes, and osteoporosis, exercise regularly, get sufficient sleep, maintain mental health, and have a balanced diet. 본 연구는 국민건강영양조사 2019년, 2021년 자료를 활용하여 전기노인 여성의 기운에 따른 건강행태와 영양상태를 비교하고자 하였다. 65-74세 전기노인 여성을 대상으로 하였으며 (n = 1,113) 기운 정도에 따라 네 그룹 (항상 기운 있음, 자주 기운 있음, 가끔 기운 있음, 전혀 기운 없음)으로 나누어 비교하였다. 사회경제적 요인에서 교육수준이 높을수록, 가구소득이 많을수록, 식생활 형편이 좋을수록, 경제활동을 하고 있는 경우에 기운이 높게 나타났다. 만성질환 유병률을 비교했을 때, 관절염, 당뇨병, 골다공증 유병의 경우 기운이 낮게 나타났다. 건강행태를 비교했을 때, 주관적 건강인지가 좋을수록, 유산소 신체활동을 실천할수록 기운이 높게 나타났다. 흡연과 음주에서는 유의적인 차이가 없었다. 정신건강 요인에서 6-8시간 정상 수면 시간일수록, 스트레스 정도가 낮을수록, 우울감이 적을수록 기운이 높았다. 식품 섭취를 비교한 결과 식품 섭취량과 감자·전분류, 버섯류, 과일류, 육류, 우유류, 동물성 유지류, 음료류 섭취량이 많을수록 기운이 높았다. 영양소 섭취를 비교한 결과 단백질, 지방, 포화지방산, 단일불포화지방산, 다가불포화지방산, n-6계 지방산, 식이섬유, 당, 인, 칼륨, 마그네슘, 철, 아연, 리보플라빈 섭취량이 많을수록 기운이 높았다. 본 연구를 통해 전기노인 여성의 기운 넘치는 생활을 위해서는 사회경제적인 안정, 관절염, 당뇨, 골다공증 등의 만성질환 예방, 운동, 충분한 수면, 정신건강, 고른 영양섭취가 필요함을 확인하였다. 본 연구 결과가 향후 전기노인 여성의 기운을 향상시키기 위한 기초자료로 활용될 수 있을 것이다.